STEROID-INDUCED ROSACEA AS A RESULT OF UNCONTROLLED SELF-MEDICATION - Nykolaichuk, Khrystyna (Collection of scientific papers «ΛΌГOΣ», 2022)
Dermatology is a safe practice: we register unpredictable outcomes so rarely. Topical treatment complications are still a significant concern nowadays because some adverse reactions are the issue of self-treatment.